How Social Exclusion Affects Consumers’ Color Preference - Zong, Lu; Wu, Shali; Duan, Shen (Frontiers in Psychology, 2022)
Social exclusion can cause negative changes on human beings both in the physiological and psychological aspects. Although considerable efforts have been devoted to study its effects on consumption behavior, little attention has been paid to the consequence that social exclusion might have on consumer’s color preference and the underlying mechanisms. Such social events can change individual’s behavior. This work examines the influence of social exclusion on consumers’ color preference as well as the moderation and mediation effects via three experiments: Experiment 1 studies the impacts of social exclusion on consumer color choice (warm color versus cold color). To further validate the robustness of the results, experiment 2 is designed by replicating the findings of experiment 1 in another product category and instructed the participants to choose products with different colors. Meanwhile, the mediation effect of self-threat is examined. In Experiment 3, the moderation effect of self-construal is investigated via a 2 (exclusion vs. inclusion) × 2 (independent vs. interdependent) × (warm color vs. cold color) between-subjects design. Our results indicate that social exclusion makes people prefer warm colors rather than cold colors. However, these effects would be mediated by self-threat, which could be further moderated by self-construal. The present study establishes the relationship between social exclusion and consumers’ color preference, which is expected to provide guidance for companies to improve product design and promotion strategies to adapt to various contexts.